Health assessment on children exposed to air pollutant PM10 in Bangalore city - Ambikapathy, Mala; Rengasamy, Murugesan; Beerappa, Ravichandran; Karunamoorthy, Panjakumar; Basappa, Nagappa (International Journal of Psychosocial Rehabilitation, 2020)
Air pollutants are present in the atmosphere in the form of any solid or gaseous substance, which are considered injurious to living system of the planet. The objectives of the study were to assess the relationship between air pollution and childhood respiratory morbidity in various identified polluted areas and the relevant morbidity conditions of children in different living conditions were evaluated. To achieve the objective of the study, a retrospective study was done for the period from January 2011 to December 2015. The morbidity conditions of the children below 14 years were collected from the Primary health centres (PHC) located near the study area. From this study it was found out that there was a statistically significant positive correlation(r=0.227, p<.01) between the levels of pollutant PM10 and the respiratory illnesses viz., cold, cough,fever, lower respiratory illness and upper respiratory illness of children. Binary logistic regression (BLR) model was employed to explore the various factors for the causes of respiratory illnesses. This model showed that the exposure of pollution level, PM10 significantly influence the respiratory illnesses and female children were found to be more sensitive. Overall explanatory variable of age group less than 5 and 6-10 years of age showed highly significant associationwith theillness. Monsoon and winter season were found to possesshighly significantassociation with the disease condition. From this study, it has been concluded that morbidity conditions of respiratory illnesses among children arestrongly associated with the pollution levels of the area.